Prototipe Sistem Pencegah Banjir dengan Pengontrolan Pintu Air Waduk menggunakan Kontrol PID berbasis PLC & HMI - Felix Udianto, Johanes; Eka Budiyanta, Nova; Nur, Tajuddin; Siregar, Marsul (Jurnal Elektro, 2023)
The purpose of research on this flood prevention system prototype design is to prevent flood caused by overflowing reservoir water. This system prototype uses the Modicon M340 Programmable Logic Controller as a controller and is equipped with a Human Machine Interface feature as a medium for managing and monitoring system performance virtually. This system is supported by a Water-Level Sensor to measure the water level in the reservoir and also the rate of addition of water in the reservoir. The sluice mechanism is driven by a Stepper Motor assisted by the ULN2003 Driver Module based on Proportional, Integral and Derivative (PID) control to maintain the water level in the reservoir. PID control in this system successfully runs optimally at constant KP = 3.5, KI = 2, and KD = 1, with an error result of 0,048%. This constant has the best response time compared to other constants, where rise time = 11.76 s, settling time = 13.95 s, and steady state time = 14.07 s.